1999
DOI: 10.2337/diabetes.48.7.1466
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala substitution in the peroxisome proliferator-activated receptor-gamma2 is not associated with type 2 diabetes.

Abstract: Peroxisome proliferator-activated receptor (PPAR)-gamma is a major regulator of adipogenesis and insulin sensitivity. The PPAR-gamma gene generates two isoforms through alternative splicing, PPAR-gamma1 and -gamma2, the latter having an additional stretch of 28 amino acids at its NH2-terminus in the ligand-independent activation domain. This extension renders PPAR-gamma2 more sensitive to insulin action. Since there is a Pro12Ala substitution in this domain, we tested whether it is related to type 2 diabetes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
5
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 8 publications
10
94
5
4
Order By: Relevance
“…In a previous study we could not ®nd an association of the Pro12Ala mutation with overweight in a population-based sample. 11 In agreement with the hypothesis that the Pro12Ala mutation plays a much stronger role in severe obesity with early onset, a very recent paper by Ek et al shows a signi®cant and positive association between the occurrence of the Pro12Ala mutation and BMI in people with severe obesity with juvenile onset, although in the condition of homozygosity. 19 As for insulin resistance we could not ®nd any association between insulin concentration, which is a marker of insulin resistance, and the Ala-mutated allele.…”
Section: Discussionsupporting
confidence: 56%
“…In a previous study we could not ®nd an association of the Pro12Ala mutation with overweight in a population-based sample. 11 In agreement with the hypothesis that the Pro12Ala mutation plays a much stronger role in severe obesity with early onset, a very recent paper by Ek et al shows a signi®cant and positive association between the occurrence of the Pro12Ala mutation and BMI in people with severe obesity with juvenile onset, although in the condition of homozygosity. 19 As for insulin resistance we could not ®nd any association between insulin concentration, which is a marker of insulin resistance, and the Ala-mutated allele.…”
Section: Discussionsupporting
confidence: 56%
“…In vitro studies showed that this allele reduces PPARg DNA binding affinity and transcriptional activity [70,73,194,195]. Although some additional studies did not support a statistically significant role for the PPARg 2 P12A polymorphism in the etiology of type 2 diabetes [196][197][198], a more recent meta-analysis of all published data, comprising more than 25 000 cases of diabetes, showed an association of P12A with type 2 diabetes [199]. The large population that was necessary in order to demonstrate the association between P12A and type 2 diabetes is due to the weak effect of the risk allele, since individuals that are homozygous for the higher risk P12 allele have only a 25% increase in diabetes risk.…”
Section: Pparg Loss Of Function Mutationsmentioning
confidence: 99%
“…The most frequently occurring PPAR-γ polymorphism is the substitution of proline to alanine (Pro12Ala) in exon B of the PPAR-γ2 gene (rs1801282), and numerous polymorphism studies have been performed on its association with type 2 diabetes mellitus, insulin resistance and obesity, although the significance of such associations remains still a debate (Fajas et al, 1997;Mancini et al, 1999;Ringel et al, 1999;Altshuler et al, 2000;Clement et al, 2000;Hara et al, 2000;Meirhaeghe et al, 2000). The next most frequently occurring PPAR-γ polymorphism is C → T substitution in exon 6 (rs3856806), which was identified by Meirhaegue et al (2000), and it was shown to have significant association with bone mineral density (BMD) in postmenopausal Japanese women (Ogawa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%